FLT3 functional low-frequency variant rs76428106-C is associated with susceptibility to systemic sclerosis. (25th July 2022) - Martínez-López, Javier; Kerick, Martin; Ortiz-Fernández, Lourdes; Acosta-Herrera, Marialbert; Márquez, Ana; Martín, Javier
Abstract: Objectives: rs76428106-C, a low frequency polymorphism that affects the splicing of the FLT3 gene, has recently been associated with several seropositive autoimmune diseases. Here, we aimed to evaluate the potential implication of rs76428106-C in the susceptibility to systemic sclerosis (SSc). Methods: We analysed a total of 26 598 European ancestry individuals, 9063 SSc and 17 535 healthy controls, to test the association between FLT3 rs76428106-C and SSc and its different subphenotypes. Genotype data of rs76428106 were obtained by imputation of already available genome-wide association study data and analysed by logistic regression analysis. Results: In accordance with that observed in other autoimmune disorders, the FLT3 rs76428106-C allele was significantly increased [ P -value = 2.03 × 10 −3, odds ratio (OR) = 1.34] in SSc patients compared with healthy controls. A similar risk effect was found when the main SSc clinical and serological subgroups were compared with controls. When comparing SSc patients with and without digital ulcers (DU), the rs76428106-C frequency was significantly increased in DU-positive SSc patients in comparison with DU-negative patients ( P -value = 0.036, OR = 2.16). Conclusion: This study is the first to report an association between rs76428176-C and SSc. Our results support the role of FLT3 as a relevant gene in seropositive immune-mediated diseases and a potential biomarker for SSc microangiopathy.